Open-World Dialog: Challenges, Directions, and a Prototype - Bohus, Dan; Horvitz, Eric (Microsoft, 2009)
We present an investigation of open-world dialog, centering on systems that can perform conversational dialog in an open-world context, where multiple people with different needs, goals, and long-term plans may enter, interact, and leave an environment. We outline and discuss a set of challenges and core competencies required for supporting the kind of fluid multiparty interaction that people expect when conversing and collaborating with other people. Then, we focus as a concrete example on the challenges faced by receptionists who field requests at the entries to corporate buildings. We review the subtleties and difficulties of creating an automated receptionist that can work with people on solving their needs with the ease and etiquette expected from a human receptionist. Finally, we review details of the construction and operation of a working prototype.